Symbolic Representation of Psychological States in the Dreams of Women with Eating Disorders - Brink, Susan M.; Allan, John A. B.; Boldt, Walter (Canadian Journal of Counselling and Psychotherapy, 2007)
The study compared the dream content of 12 eating-disordered (ED) and 11 non-eating-disordered (NED) women using the Marascuilo method of pairwise comparisons. The results showed significant links in the dreams of the ED group between the presence of an eating disorder and a sense of ineffectiveness, the presence of self-hate, a sense of being controlled by others, a sense of being watched and judged, an inability to self nourish, and the presence of negative emotions. A sense of ineffectiveness was significantly paired with the presence of anger and negative emotions in the ED group. There were no significant pairings in the NED group. Dream examples are given to illustrate the findings. Implications for counselling are discussed in terms of aspects of self that emerge via dreams, and what techniques can intensify these experiences in the counselling setting.